Experience with anterior resection for rectal cancer. One case with rapid local recurrence and one case with cancer regression after preoperative radiation - Marijata Marijata (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
During three years periode from August 1989 to August 1992 eight patients underwent anterior resection for rectal cancer, five patients in Sardjito Central General Hospital and three patients in Patmasuri Special Surgery Hospital. Five patients with high rectal cancer and three patients with middle rectal cancer underwent anterior and low anterior resection respectively. Intestinal obstruction due to local recurrence occured four months after operation in oae patient who underwent low anterior resection and cancer regression after preoperative radiation occured pathologically in one patient.Key W ords: high rectal cancer anterior resection middle rectal cancer low anterior resection cancer regression